Socio-Economic Conditions of Workers of Fireworks Industry in Viridhunagar District - Chandra Bose, S.; Balamurugan, P. K.; Velmurugan, R. (Indian Journal of Marketing, 2009)
Socioeconomics is the study of the relationship between economic activity and social life. In many cases, however, socioeconomists focus on the social impact of some sort of economic change. These may affect patterns of consumption, the distribution of incomes and wealth, the way in which people behave (both in terms of purchase decisions and the way in which they choose to spend their time), and the overall quality of life. The goal of socioeconomic study is generally to bring about socioeconomic development, usually in terms of improvements in metrics such as GDP, life expectancy, literacy, levels of employment, etc. The socio-economic condition of the people indicates the overall status of the country. Basically India is an agriculture-based country, where majority of the people are living in rural areas and doing agricultural work for their livelihood. The study area namely Virudhunagar district, is also primarily an agricultural area. Apart from agricultural activities, the people pursue doing match works, fireworks, printing works and the like. Virudhunagar district provides employment opportunity to the fireworks workers throughout the year, the economic status of the people engaged in fireworks activities is not encouraging due to the reason that workers are cheaply available and therefore paid comparatively little wages. In this connection, an attempt has been made to study the socio-economic background of the workers of fireworks industry in Virudhunagar district.